Teachers' epistemic beliefs and reported practices in two cultural contexts - Lammassaari, Heidi; Hietajärvi, Lauri; Lonka, Kirsti; Chen, Sufen; Tsai, Chin-Chung (Educational studies, 2024)
Teachers' epistemic beliefs may have consequences for their pedagogical work. We used previously developed scales to assess epistemic beliefs that teachers hold about learning, knowledge and knowing, and how they report putting such ideas into practice. The scales consisted of self-reported Likert-type statements considering collaborative knowledge building, valuing metacognition, certainty of knowledge, and a surface approach to learning. The participants were 127 subject-matter teachers from Finland and 97 teachers from Taiwan. Based on previous research, we constructed a confirmatory factor analysis (CFA) model for the Finnish sample and replicated this with the Taiwanese sample. We confirmed two factors: 1) reflective-collaborative theory (consisting of collaborative knowledge building and valuing metacognition scales) and 2) knowledge transmission theory (consisting of certainty of knowledge and simple learning scales) in both samples. In conclusion, essential and corresponding aspects of teachers' epistemic beliefs and their reported practices were found. However, the results showed some cross-cultural variance. It is important to look at teachers' epistemic beliefs because they may have consequences for teachers' pedagogical work. These beliefs are a part of epistemic cognition which in this context consists of epistemic beliefs (beliefs about knowledge and learning) and how teachers report to put them into practice (e.g.). The aim of this study is to identify and assess teachers' core epistemic beliefs and how such beliefs are associated with their practical ideas on pedagogy in two diverse cultural contexts. We used previously developed scales to assess beliefs that teachers hold about learning, knowledge and knowing, and how they report putting such ideas into practice. The scales consisted of self-reported Likert-type statements considering collaborative knowledge building, valuing metacognition, emphasising certainty of knowledge, and a surface approach to learning. The participants were 127 subject-matter teachers from Finland and 97 teachers from Taiwan. Based on previous research, we constructed a confirmatory factor analysis (CFA) model for the Finnish sample and replicated this with the Taiwanese sample. We confirmed two factors: 1) reflective-collaborative theory (consisting of collaborative knowledge building and valuing metacognition scales) and 2) knowledge transmission theory (consisting of certainty of knowledge and simple learning scales) in both samples. In conclusion, essential and corresponding aspects of teachers' epistemic beliefs and their reported practices were found. However, the results showed some cross-cultural variance.